RESPONSE TO NEOADJUVANT THERAPY AND LONG-TERM OUTCOME IN PATIENTS WITH TRIPLE NEGATIVE BREAST CANCER - Hegmane, Alinta; Liepniece-Karele, Inta (European Scientific Journal, ESJ, 2014)
Background. Triple negative breast cancer (TNBC) is defined by thelack of estrogen receptors (ER), progesterone receptors (PR) and humanepidermal growth factor receptor 2 (HER-2) expression. In this study weinvestigated response to neoadjuvant chemotherapy in TNBC patients and itsimpact on disease free (DFS) and overall survival (OS).Patients and methods. We identified 134 patients with stage I-III TNBCtreated at Riga East University Hospital between 2009-2012. 48 patients withTNBC received neoadjuvant chemotherapy. Correlation of clinical andpathological parameters with pathologic complete response (pCR) rate,disease-free and overall survival measurements and organ specific relapserates were analysed.Results. 48 patients with stage IIB-IIIC TNBC were included, 17 patientsreceived anthracycline based, 31 patients anthracycline and taxane basedneoadjuvant chemotherapy. 8 patients (16%) had pCR, 38 patients hadincomplete response, 2 patients had disease progression during neoadjuvantchemotherapy. pCR correlates with primary tumor size, but not with otherclinical and pathological factors. At a median follow-up of 30 months, 100%patients who reached pCR were disease-free versus 55% in those withoutpCR (p=0.017). Overall survival was 100% in patients who had pCR versus50% in those without pCR (p=0.020). 2 patients are alive after diseaserecurrence, 20 patients died. The most common sites of disease recurrencewere brain, lung and liver.Conclusions. Patients with TNBC who have a pCR in the breast and axillarynodes have a significantly improved disease-free and overall survival ratecompared with patients with residual disease after neoadjuvantchemotherapy.